Integrated effect of bio-organics with chemical fertilizer on growth, yield and quality of cabbage (Brassica oleracea var capitata) - VERMA, RAJHANS; MAURYA, B R; MEENA, VIJAY SINGH (The Indian Journal of Agricultural Sciences, 2014)
This experiment focused on the effects of Pseudomonas fluorescens and humic acid in combination with three different levels of fertilizers on growth, yield and quality traits of Brassica oleracea L. Results indicated that treatments comprising 100% recommended fertilizers package coupled with seedling treated with Pseudomonas fluorescens and humic acid caused significantly higher plant height, dry matter in leaves (head), higher number of non-wrapper leaves and head yield (54.38 tonnes/ha) over 50% recommended dose of fertilizer with Pseudomonas fluorescens applied. Treatment 50% recommended dose of fertilizer applied with Pseudomonas fluorescens and humic acid was at par with 100% recommended dose of fertilizer alone. Total carbohydrate content in head (40.46%) was significantly higher with use of 100% recommended dose of fertilizer with Pseudomonas fluorescens and humic acid. Maximum protein content (18.54%) was noticed with application of 100% recommended dose of fertilizer with Pseudomonas fluorescens and humic acid that was 10.90% higher than recommended dose of fertilizer alone. Fibre content in head was improved remarkably with the use of Pseudomonas fluorescens and humic acid. Significantly higher content of ascorbic acid (34.51 mg/100 g) in head was also registered with application of 100% recommended dose of fertilizer with Pseudomonas fluorescens and humic acid.